2020
DOI: 10.1155/2020/7375136
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Melatonin on Aluminum-Induced Hepatotoxicity and Nephrotoxicity in Rats

Abstract: Aluminum (Al) is a ubiquitous element with known toxicity for both humans and animals. Herein, we aimed to investigate the potential role of melatonin (MEL) in hepatotoxicity and nephrotoxicity following aluminum chloride (AlCl3) treatment in rats. Adult male rats were treated with AlCl3 (34 mg/kg bwt) for eight weeks. Exposure to AlCl3 enhanced the serum activities of the liver transaminases (alanine aminotransferase and aspartate aminotransferase) and increased the level of bilirubin, in addition to the seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 46 publications
9
39
0
2
Order By: Relevance
“…SOD, CAT, and GPx form the first line of defense against ROS, and decrease in their activities contributes to oxidative stress in tissues. GSH is a key non‐enzymatic antioxidant that binds to and eliminates oxidative agents, and decreases in its levels have been associated with changes in the oxidative stress response (Othman et al., 2020). SOD is an antioxidant that eliminates singlet oxygen and converts superoxide radicals to hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…SOD, CAT, and GPx form the first line of defense against ROS, and decrease in their activities contributes to oxidative stress in tissues. GSH is a key non‐enzymatic antioxidant that binds to and eliminates oxidative agents, and decreases in its levels have been associated with changes in the oxidative stress response (Othman et al., 2020). SOD is an antioxidant that eliminates singlet oxygen and converts superoxide radicals to hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…The tryptophan-derived hormone melatonin—often viewed as a nutraceutical insomuch as it can be administered orally and is sold in capsule form over-the-counter—has phase 2 activity that appears to reflect up-regulation of nrf2 at the transcriptional level [ 86 , 87 , 88 ]. This may reflect the fact that the promoter of the nrf2 gene contains E boxes that bind the “clock” transcription factor Bmal1, in conjunction with the protein Clock, and this drives nrf2 transcription [ 89 , 90 ].…”
Section: Nlrp3 Inflammasome Suppression Via Phase 2 Inductionmentioning
confidence: 99%
“…Changes in mitochondrial respiration are well-known to contribute to metabolic remodeling, although the mechanism of action involved in melatonin-driven tumoral death remains unclear. Moreover, previous studies showed that melatonin not only enhances the oncostatic effects of radio-or chemotherapy on tumor cells, but also protects normal cells against the adverse effects of these treatments [10,12,14,15].…”
Section: Introductionmentioning
confidence: 99%